Insights on the SARS-CoV-2 genome variability: the lesson learned in Brazil and its impacts on the future of pandemics. Issue 11 (3rd November 2021) - Grosche, Victória Riquena; Santos, Igor Andrade; Ferreira, Giulia Magalhães; Dutra, João Victor Rodrigues; Costa, Larissa Catharina; Nicolau-Junior, Nilson; Queiroz, Artur Trancoso Lopo; José, Diego Pandeló; Jardim, Ana Carolina Gomes
Abstract : Since the beginning of the SARS-CoV-2 spread in Brazil, few studies have been published analysing the variability of viral genome. Herein, we described the dynamic of SARS-CoV-2 strains circulating in Brazil from May to September 2020, to better understand viral changes that may affect the ongoing pandemic. Our data demonstrate that some of the mutations identified are currently observed in variants of interest and variants of concern, and emphasize the importance of studying previous periods in order to comprehend the emergence of new variants. From 720 SARS-CoV-2 genome sequences, we found few sites under positive selection pressure, such as the D614G (98.5 %) in the spike, that has replaced the old variant; the V1167F in the spike (41 %), identified in the P.2 variant that emerged from Brazil during the period of analysis; and I292T (39 %) in the N protein. There were a few alterations in the UTRs, which was expected, however, our data suggest that the emergence of new variants was not influenced by mutations in UTR regions, since it maintained its conformational structure in most analysed sequences. In phylogenetic analysis, the spread of SARS-CoV-2 from the large urban centres to the countryside during these months could be explained by the flexibilization of social isolation measures and also could be associated with possible new waves of infection. These results allow a better understanding of SARS-CoV-2 strains that have circulated in Brazil, and thus, with relevant infomation, provide the potential viral changes that may have affected and/or contributed to the current and future scenario of the COVID-19 pandemic.